Application of multiple intelligences teaching approach in classroom instruction based on POMAT model - Sulaiman, Suriati; Sulaiman, Tajularipin (Universiti Putra Malaysia Press, 2012)
Instructional practices, particularly in Malaysian secondary schools, have undergone tremendous transformation in order to achieve Vision 2020. Part of it is the use of various teaching approaches in classroom instruction as an effort to help the students comprehend the curriculum content better. One of the major teaching approaches which is widely used in Malaysian secondary schools is Multiple Intelligences Teaching Approach or collectively known as MITA. Hence, a qualitative research was conducted to look at teachers’ instructional practices in employing multiple intelligences in classroom instruction. Research subjects were six English teachers who serve as informants. Data were collected from classroom observations, semi-structured in-depth interviews and document analysis. Classroom observations were conducted to record the actual classroom instruction that took place in English reading comprehension classrooms while semi-structured in-depth interviews were administered to obtain precise information from the informants. Raw data were recorded and transcribed manually. Later, the data were analysed interpretively and descriptively based on the themes that emerged from research findings. Meanwhile, triangulating data was done to ascertain the validity and reliability of the findings. The study unveiled the application of multiple intelligences teaching approach in classroom instruction at some secondary schools in Pahang based on the POMAT model. Important aspects being explored included the application of multiple intelligences in instructional procedure, instructional objective, instructional material, classroom assessment and instructional technology.